Emerging Trends in International Development and Climate Policy
XV, 156 p. 3 illus., 2 illus. in color.
Keywords: This open access book delves into the considerable alignment of global sustainable development priorities between Germany and the Republic of Korea (hereafter referred to as Korea), despite their geographical separation. Notably, both nations share a common commitment to development policy and international climate action, an alignment that holds immense potential for enhanced cooperation in today’s evolving global landscape. Germany’s historical role as a founding member of the international development cooperation system juxtaposes with Korea’s more recent entry into the Organisation for Economic Co-operation and Development (OECD) and its Development Assistance Committee (DAC) in 2010. Korea has transformed from a significant development assistance recipient to an active provider, a transition mirrored in its engagement in international climate finance. Within this dynamic context, the book thoroughly examines key aspects such as the evolving development policy profiles of Germany and Korea, their roles in international organizations, and their shared commitment to international climate policies. It also explores avenues for deeper collaboration between these like-minded partners, all against the backdrop of an evolving geopolitical focus, including the new Indo-Pacific emphasis. Stephan Klingebiel is Head of the Research Programme “Inter- and transnational cooperation” at the German Institute of Development and Sustainability (IDOS) and a Visiting Professor at Ewha Womans University, Seoul, and at the University of Turin. Thomas Kalinowski is Professor at the Graduate School of International Studies, Ewha Womans University, Seoul, Korea. Niels Keijzer is Senior Researcher and Project Lead at the German Institute of Development and Sustainability (IDOS).